Numerical analyses for improved hydrodynamics of deep water torpedo anchor - Soh, B.P. (Institute of Physics Publishing, 2015)
The literature shows a lack on well established guidelines on the design of the torpedo anchors. This research aims to investigate the effect of various geometric parameters in the torpedo anchors' design to optimize for higher terminal velocity. A CFD model was developed and simulations were carried out using ANSYS FLUENT commercial software. Consequently, correlations between various parameters and its resultant drag coefficient were developed. The parameters of interest included geometric changes of the original design, as well as sea water properties that reflect water depth in South China Sea. New design features are proposed and investigated in the overall parametric studies. As a result, it was found that the terminal velocity can be improved by sharper tip angle, greater aspect ratio, greater diameter ratio, and an optimum rear angle of 30Â°. Clear relationships between each factor and its resulted terminal velocity were developed. More importantly, the sensitivity of drag coefficient towards each of the parameters was predicted.